2017
DOI: 10.1093/cercor/bhx048
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of White Matter Tracts by Diffusion MR Tractography in Cat and Ferret that Have Similar Gyral Patterns

Abstract: The developmental relationships between gyral structures and white matter tracts have long been debated, but it is still difficult to discern whether they influence each other's development or are causally related. To explore this topic, this study used cats and ferrets as models for species that share similar gyral folding patterns and imaged with diffusion magnetic resonance imaging to compare white matter innervations in homologous gyri and other brain regions. Adult cat and ferret brains were analyzed via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 66 publications
1
7
0
Order By: Relevance
“…Tractography algorithms can lead to false connections or premature terminations of tracked fibers and thus be responsible for an anatomical inaccuracy between MRI-derived reconstruction and dissection (43). Similarly to our findings regarding the inferior fronto-occipital fasciculus, reconstruction of tracts that could not be identified on gross anatomical dissection has already been reported for the feline inferior fronto-occipital fasciculus (24,25,27,35) and the human superior fronto-occipital fasciculus (44,45). For this latter fasciculus, modeling errors are assumed to have generated false continuations between different projection fibers, thus leading to the reconstruction of a continuous fronto-occipital fiber bundle (45).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Tractography algorithms can lead to false connections or premature terminations of tracked fibers and thus be responsible for an anatomical inaccuracy between MRI-derived reconstruction and dissection (43). Similarly to our findings regarding the inferior fronto-occipital fasciculus, reconstruction of tracts that could not be identified on gross anatomical dissection has already been reported for the feline inferior fronto-occipital fasciculus (24,25,27,35) and the human superior fronto-occipital fasciculus (44,45). For this latter fasciculus, modeling errors are assumed to have generated false continuations between different projection fibers, thus leading to the reconstruction of a continuous fronto-occipital fiber bundle (45).…”
Section: Discussionsupporting
confidence: 79%
“…As DTI tractography assesses the structural integrity of white matter, it has been widely used for prognostic and/or diagnostic purposes in various brain pathologies such as stroke (3)(4)(5)(6), neurodegenerative diseases (7)(8)(9)(10)(11), and brain tumors (12). With the increasing availability of high-field-strength MRI (1.5 and 3 T) in veterinary facilities (13)(14)(15)(16)(17), the use of this technique is now gradually growing for the description of white matter anatomy and structural connectivity of domestic mammals (dog, cat, ferret, and sheep) (18)(19)(20)(21)(22)(23)(24)(25)(26)(27). These collected anatomical data are of particular interest as they might have applications in both veterinary medicine and experimental research.…”
Section: Introductionmentioning
confidence: 99%
“…The inferior fronto-occipital fasciculus is not included in the atlas, as it was not identified even with liberal seed regions placed over the entire frontal and occipital regions. This fasciculus has been previously reconstructed in the feline using tractography (Jacqmot et al, 2017;Das and Takahashi, 2018). Although neuroanatomical connectivity analysis of the cat has shown both efferent and afferent connection between frontal and occipital regions (Scannell et al, 1995), the presence of a fronto-occipital fasciculus has not been identified on gross anatomic dissection (Pascalau et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Recent pioneering studies using diffusion MR tractography reported that ferrets (Mustela putorius furo), like humans and monkeys, also have abundant U-fibers [23,24]. Ferrets have a long history in research and have relatively well-developed brain structures such as cortical folds (i.e.…”
Section: Introductionmentioning
confidence: 99%